Correlation of the complementary virtual test of computer-simulated clinical cases with the classic OSCE and with the MIR score. - Toala Mora, Ana Mikal (Spanish Journal of Medical Education, 2026)
The article analyzes the relationship between the Complementary Virtual Clinical Test (PVCC), the traditional OSCE, and the MIR examination, showing that PVCC has a moderate and more consistent correlation with MIR than the local OSCE. This suggests that each assessment tool measures different dimensions of clinical competence. This finding is particularly relevant given that the MIR has been criticized for prioritizing theoretical knowledge over practical, communicative, and attitudinal skills. Additionally, the low correlation between clinical rotation grades and standardized tests highlights the variability inherent in tutor-based and heterogeneous clinical settings, reinforcing the need to incorporate objective assessment tools such as the OSCE. Sex-related differences were also identified, with males performing better on PVCC and MIR, and females excelling in clinical history taking and clinical rotations. Although these findings should be interpreted cautiously, they open important lines of research regarding learning styles and competency profiles. Consistent with previous studies, the OSCE demonstrates predictive validity; however, its correlation with MIR remains moderate, confirming that both instruments are complementary rather than redundant. In conclusion, the study supports a multimodal assessment approach integrating multiple evaluation methods to achieve a more comprehensive appraisal of medical students’ competencies and to reconsider evaluation criteria in clinical rotations.